PERAN SUPERVISI KEPALA SEKOLAH DI SMP NEGERI 12 HALMAHERA TENGAH - Faisal Y Habsyi; Anita Usman (Program Studi Pendidikan Ekonomi STKIP Kie Raha Ternate, 2021)
Supervision aims to guide and foster teachers to become professional teachers. With a professional teacher, the goal of improving student learning outcomes will be achieved. It is the principal's job as a supervisor to assist teachers in improving their teaching abilities. This research is specifically to find out how the role of principal supervision in SMP Negeri 12 Halmahera Tengah is. This study uses a descriptive qualitative approach, collecting data using participant observation, interviews and documentation techniques. The results show that 1). The role of the Principal of SMP Negeri 12 Halmahera Tengah is still low, this is because the Principal prioritizes other roles so that the role of supervision is neglected. 2). The lack of supervision by the principal has resulted in the low performance of teachers at SMP Negeri 12 Halmahera Tengah. 3) There needs to be local government attention in terms of encouraging school principals to carry out the principal's role optimally and comprehensively, especially the role of supervision. Because the role of supervision determines the quality of education in a school.